2017
DOI: 10.3390/min7070107
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Coke Ratio on the Sintering Behavior of High-Chromium Vanadium-Titanium Magnetite

Abstract: High-chromium vanadium and titanium magnetite (HCVTM) sinter has poor properties. The coke ratio has an important effect on the behavior of HCVTM sintering as it affects the mineral phases in the high-chromium vanadium and titanium sinter (HCVTS) via changing the sintering temperature and atmosphere. In this work, the sintering behavior of HCVTM mixed with varying coke ratios was investigated through sintering pot tests, X-ray diffraction (XRD), gas chromatographic analysis, and mineral phase analysis. The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…Subsequently, the distribution of the mineral phases became disordered. Our previous research [4,5,[23][24][25] found that, when the MgO content was 2.66%, a large number of secondary skeleton hematites were produced. The distribution of the mineral structures were non-uniform and the partial phases were in a slightly over-molten state, as shown in Figure 7a.…”
Section: Operation Parameters Of Sintering Processmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, the distribution of the mineral phases became disordered. Our previous research [4,5,[23][24][25] found that, when the MgO content was 2.66%, a large number of secondary skeleton hematites were produced. The distribution of the mineral structures were non-uniform and the partial phases were in a slightly over-molten state, as shown in Figure 7a.…”
Section: Operation Parameters Of Sintering Processmentioning
confidence: 99%
“…Chromium and vanadium resources have been extracted from CCVTM [1][2][3][4][5][6][7]. The viscosity and the TiO 2 content of the slag are high in the blast furnace (BF) iron-making process, due to the high TiO 2 content in the CCVTM.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, with the continuous advancement of mining technology and soaring mineral resource prices, the value of the large amount of low-grade vanadiferous titanomagnetite ore (LVTM) identified within the mine production areas has been highlighted by steel companies. The LVTM resources in the Chengde area have been estimated to exceed 10 billion tons [6][7][8][9]. Multiple studies have been done on conventional VTM, while fewer studies on LVTM with complex phase compositions and different properties are available [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…In order to use CVTM efficiently, the sintering behaviors of CVTM have been proposed by the authors' laboratory [7][8][9]. In the BF process, the CVTM sinter with different basicity, coke ratios, and MgO contents have been studied.…”
Section: Introductionmentioning
confidence: 99%
“…In the BF process, the CVTM sinter with different basicity, coke ratios, and MgO contents have been studied. Yang [7,8] studied the effects of coke ratios and MgO on the sintering behaviors and the metallurgical properties of CVTM. Yang [9] surveyed the effect of basicity on the mineral compositions and elements migration of CVTM sinters.…”
Section: Introductionmentioning
confidence: 99%